Determining the Activation Energy of Solid-State Phase Transformation of 1035 Steel from Isoconversional Analysis of DSC Data. Issue 1 (March 2020) - Tan, G L; Tang, D; Mu, T; Li, Z; Xu, J X; Wang, X M
Abstract: The results of solid-state phase transformation kinetics analysis for the steel have been controverted because of the complexity and diversity. In this paper, the activation energy, which represents the energy barrier for austenite to pearlite solid-state phase transformation of 1035 steel, was determined from the nonlinear isoconversional method. The result shown that the activation energy is change with the degree of transformation. Therefore, the nonlinear isoconversional approach maybe a better way to calculate the activation energy of solid-state phase transformation.